2015
DOI: 10.1016/j.nbd.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mechanisms contribute to the neurological manifestations of tuberous sclerosis complex

Abstract: Epilepsy and other neurological deficits are common, disabling manifestations of the genetic disorder, Tuberous Sclerosis Complex (TSC). Brain inflammation has been implicated in contributing to epileptogenesis in acquired epilepsy due to brain injury, but the potential role of inflammatory mechanisms in genetic epilepsies is relatively unexplored. In this study, we investigated activation of inflammatory mediators and tested the effects of anti-inflammatory treatment on epilepsy in the Tsc1-GFAP conditional k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 52 publications
3
47
0
2
Order By: Relevance
“…Inflammation has been previously documented in TSC lesions, both in the brains of TSC animal models and in patient tissues59606162. Work from Zhang et al 62. suggested that this inflammation is directly related to hyperactive MTORC1 signalling and is not merely a result of seizure activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Inflammation has been previously documented in TSC lesions, both in the brains of TSC animal models and in patient tissues59606162. Work from Zhang et al 62. suggested that this inflammation is directly related to hyperactive MTORC1 signalling and is not merely a result of seizure activity.…”
Section: Discussionmentioning
confidence: 97%
“…We used these molecular tools to detect neuroinflammation associated with TSC brain lesions. Inflammation has been previously documented in TSC lesions, both in the brains of TSC animal models and in patient tissues59606162. Work from Zhang et al 62.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently found evidence that inflammatory changes may contribute to epileptogenesis in a mouse model of TSC, Tsc1 GFAP CKO mice. Antiinflammatory treatments, which reduced cytokine and chemokine production, caused a moderate inhibition of seizure progression in this mouse model . Although astrocytes may play a central role in mediating inflammatory mechanisms and epileptogenesis in Tsc1 GFAP CKO mice, microglia may also be involved in reactive inflammatory changes in the brain.…”
mentioning
confidence: 81%
“…Real‐time quantitative RT‐PCR was used to assay inflammatory cytokine and chemokine markers, C‐C motif chemokine ligand 2 (CCL2), Interleukin 1 beta (IL‐1 β) and C‐X‐C motif chemokine ligand 10 (CXCL10), as described previously . Total RNA was prepared from brains of 4‐week‐old Tsc1 GFAP CKO or control mice.…”
Section: Methodsmentioning
confidence: 99%
“…Por outro lado, camundongos com nocaute condicional de Tsc1 em células que expressam GFAP não apresentam crises convulsivas mas têm, na quarta semana pós-natal, um aumento da expressão de fatores envolvidos em processo inflamatório no cérebro (ZHANG et al, 2015). TSC1 e TSC2 são necessárias para uma resposta completa contra o estresse do retículo endoplasmático, o que sugere papel dessas proteínas na resposta a proteínas mal dobradas e sobrevivência celular (KANG et al, 2011).…”
Section: Assim Como Tsc2 Tsc1 é Regulada Por Diferentes Vias (Figuraunclassified